The Role of the Electronic Village Samsat Application (E-SAMDES) in Increasing Regional Original Revenue of Lampung Province - Muhammad Nurdian Sandri; M. Oktavianur (PT. Altaf Publishing Corp, 2026)
This study aims to analyze the implementation of the Village Electronic Samsat Application (E-SAMDES) in increasing Lampung Province's Regional Original Revenue (PAD) through Motor Vehicle Tax (PKB). The study uses a descriptive qualitative approach with an analysis of the George C. Edward III Policy Implementation Model which includes aspects of communication, resources, implementer disposition, and bureaucratic structure. Data were obtained through in-depth interviews, observation, and documentation of 13 informants consisting of officials of the Lampung Province Regional Revenue Agency, BUMDes officers, and taxpayers. Data analysis techniques were carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that the implementation of E-SAMDES has been running since 2022 and provides easy access to PKB payments for village communities. However, the contribution of PKB realization through E-SAMDES is still very low, namely below 1% of the total realization of PKB in Lampung Province during the 2022–2025 period. This condition indicates that E-SAMDES has not yet functioned as a primary instrument in increasing regional tax revenue. Implementation barriers primarily lie in uneven policy communication, limited human resources and infrastructure, less-than-proactive implementation, and suboptimal bureaucratic coordination. These findings underscore the need for systematic policy implementation strengthening to optimize E-SAMDES's contribution to PAD.